2007
DOI: 10.1029/2006jb004481
|View full text |Cite
|
Sign up to set email alerts
|

Are asperity patterns persistent? Implication from large earthquakes in Papua New Guinea

Abstract: [1] We studied the distribution of asperities for large recent earthquakes along the New Britain trench, Papua New Guinea, to investigate if they are the same for repeated ruptures of the subduction boundary. We determined the slip distributions of two earthquakes (M w $ 8) in 1971 using P diff waveforms, and an earthquake (M w 7.9) in 1995 using direct teleseismic P waves. Combining these findings with previous results for two earthquakes (M w $ 7.5) in 2000, we compared the source areas and asperity distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
(57 reference statements)
0
38
0
Order By: Relevance
“…This is likely the main reason that neither the slippredictable nor the time-predictable models apply, and why the 2007 earthquakes didn't grow as big as in 1833. This adds to the view that seismic asperities are probably not permanent features 29 but rather move around from one rupture to another within the area that is locked in the interseismic period.…”
mentioning
confidence: 92%
“…This is likely the main reason that neither the slippredictable nor the time-predictable models apply, and why the 2007 earthquakes didn't grow as big as in 1833. This adds to the view that seismic asperities are probably not permanent features 29 but rather move around from one rupture to another within the area that is locked in the interseismic period.…”
mentioning
confidence: 92%
“…And this problem is relevant not only for the Parkfield sequence. Other earthquake sequences are also similarly short (e.g., Okada et al, 2003;Park and Mori, 2007). Studying sequences of smaller events also has intrinsic difficulties.…”
Section: Parkfield Sequencementioning
confidence: 99%
“…The source characteristics of the 2009 Irian Jaya earthquake doublet are very similar to the Solomon Islands doublets ( Fig. 1 and Table 1), as described by Lay and Kanamori (1980) and Park and Mori (2007). Lay and Kanamori (1980) first noted that large shallow earthquakes in the Solomon Islands and New Britain Islands regions tend to occur in closely related pairs.…”
Section: January 3 2009 22:43 Ut Eventmentioning
confidence: 60%
“…The New Britain and Solomon Islands regions located east of the Irian Jaya region are also well known for large shallow thrust events (M w > 7.0) that have tendency to occur in closely related pairs (Table 1). These earthquake doublets are represented by the similarly sized events that occur at nearly the same time and location (Lay and Kanamori, 1980;Schwartz et al, 1989;Park and Mori, 2007). Lay and Kanamori (1980) reported that such a doublet behavior is a true characteristic of the regions due to the complex tectonic settings.…”
Section: Introductionmentioning
confidence: 99%